Antibacterial Effect of High-Purity Nisin Alone and in Combination with D-Amino Acids or Chlorhexidine in an Endodontic-Like Biofilm Model - Ericka T. Pinheiro; Lamprini Karygianni; Thomas Attin; Thomas Thurnheer (MDPI AG, 2021)
New strategies to eradicate endodontic biofilms are needed. Therefore, we evaluated the effect of high-purity nisin alone and in combination with D-amino acids (D-AAs) or chlorhexidine (CHX) against an "endodontic-like" biofilm model. Biofilms were grown on hydroxyapatite discs for 64 h and treated with nisin, eight D-AAs mixture, nisin + eight D-AAs, 2% CHX, and nisin + 2% CHX. After the 5 min and 24 h treatments, biofilm cells were harvested and total colony-forming units were counted. Differences between groups were tested by two-way ANOVA followed by Tukey's multiple comparisons test (p < 0.05). Nisin and D-AAs, alone or in combination, were not effective in reducing bacteria after short or long exposure times. After 5 min, treatment with 2% CHX and nisin + 2% CHX resulted in 2 and 2.4-log cell reduction, respectively, compared with the no treatment control (p < 0.001). After 24 h, 2% CHX and nisin + 2% CHX drastically reduced bacterial counts. In conclusion, high-purity nisin alone or in combination with D-AAs did not show antibacterial activity against multispecies biofilms. Moreover, combined treatment using nisin and CHX showed similar antibiofilm activity compared with the use of CHX alone.